Can a prison be self-managed?: a study of the informal organisation of a bolivian prison - Iudici, Antonio (Crime, law and social change, 2021)
The purpose of this study is to investigate the unique prisons of Bolivia. Their main features include the presence of wives and children, self-management of activities within the prison and the opportunity for inmates to take part in various activities. In particular, the general organisation of the prisons and the inmates’ experience, especially on an interpersonal level, is described in this study. The obtained data shows that functional and effective experiences of social rehabilitation can be promoted even under extreme conditions and, in some cases, this provides important insights into the prison systems of most developed countries.